Modelagem numérica e análise comparativa em vigas I protendidas constituídas de UHPFRC - Calori, Leonardo Mateus (2021)
Ultra-high performance fiber reinforced concrete (UHPFRC) is a material that was developed for applications that require special properties, such as compressive strengths greater than 130 MPa, high durability, satisfactory ductility in bending, and low porosity. The addition of metallic and/or synthetic microfibers to a dense, pore-free matrix promotes increased ductility and tensile strength, mitigating fragile and unannounced failures. For this reason, it is a material that has been studied to have its most recurrent application in Brazilian infrastructure. To better understand the behavior of these structures, many numerical studies have been carried out to investigate the failure behavior of beams when subjected to different types of stress. The present work has as objective to carry out the modeling and numerical simulation, in prestressed I-beams, in infinite elements and to compare the obtained resistance results with the analytical calculation predictions. Therefore, the PCI AASTHO / I profile with reduced cross-section was adopted as a reference; and the constituent models of Concrete Damage Plasticity (CDP); and beam models with class C30 and C70 concrete for comparison of results. The main results are the response of beams subjected to bending under monotonic loading; analysis of the damage pattern of the models; and verify the validity of the constitutive models implemented in the software.